Adolescent mentalizing and childhood emotional abuse: implications for depression, anxiety, and borderline personality disorder features - Martin-Gagnon, Gabriel; Normandin, Lina; Fonagy, Peter; Ensink, Karin (Frontiers in Psychology, 2023)
Background There is preliminary evidence that childhood emotional abuse (CEA) is a risk factor for adolescent mentalizing difficulties (Uncertainty/Confusion about mental states) and borderline personality features and that Uncertainty/Confusion about mental states mediate the relationship between CEA and adolescent borderline personality features, but these findings need replication. Furthermore, no previous studies have examined the relationship between adolescent mentalizing deficits, anxiety, and depression in the context of CEA. Objectives This study examined the associations between CEA, adolescent borderline personality features, depression and anxiety symptoms and tested a pathway model where Uncertainty/Confusion about mental states mediates the relationships between CEA and adolescent borderline personality features, depression and anxiety symptoms. Method A clinical sample of 94 adolescents completed the Reflective Function Questionnaire for Youth (RFQY) to assess mentalizing, the Childhood Experiences of Care and Abuse Questionnaire (CECA-Q), the Borderline Personality Disorders Features Scale (BPFS-C), and the Beck Youth Inventories for Depression (BDI-Y) and Anxiety (BAI-Y). Results Uncertainty/Confusion about mental states partially mediated the relationship between CEA and borderline traits as well as anxiety. In addition, there was an indirect effect where CEA predicted Uncertainty/Confusion about mental states, which then predicted depression. Discussion The findings are consistent with the mentalizing model of psychopathology and provide new evidence that Uncertainty/Confusion about mental states might be a critical mentalizing deficit that characterizes the associations between CEA and adolescent BPD features and depression and anxiety symptoms. Uncertainty/Confusion may be a transdiagnostic risk factor for adolescent psychological distress and dysfunction. We discuss the clinical implications.